Auditory brainstem implant pitch discrimination and auditory outcome. Issue 1 (31st December 2022) - Hallin, Karin; Rask-Andersen, Helge
Abstract: We present a pitch discrimination test performed by five experienced adult auditory brainstem implant (ABI) users with neurofibromatosis type 2 (NF2). The ability to discriminate frequency/pitch from different channels on the implant may be an important factor in improving speech performance. The pitch discrimination ability was evaluated by using a triangle test compared to adjacent contacts and the speech perception was measured by the Swedish three-digit test. The test was easy to perform, and all patients were able to answer reliably, even though it cannot be ruled out that patients used attributes other than pitch to differentiate between sounds. Due to the limited number of patients and small variation in results, no conclusive correlations could be made regarding pitch discrimination and auditory outcome. There was a tendency for poorer ability to discriminate pitch (discrimination of tonotopically adjacent electrodes) at testing to result in poorer speech results.